Analysis of the cattle movement network and its association with the risk of bovine tuberculosis at the farm level in Castilla y Leon, Spain. Issue 1 (16th October 2018) - Pozo, Pilar; VanderWaal, Kimberly; Grau, Anna; de la Cruz, Maria Luisa; Nacar, Jesus; Bezos, Javier; Perez, Andres; Minguez, Olga; Alvarez, Julio
Abstract: Between‐farm transmission of bovine tuberculosis (bTB) occurs mostly through fence‐to‐fence contact between neighbouring farms, endemic infected wildlife or movement of infected animals. Unfortunately, bTB detection is frequently delayed and identification of the source of introduction is often difficult, particularly in endemic regions. Here, we characterized the cattle movement network of Castilla y Leon, a high bTB‐prevalence (1.9% at the farm level in 2015) region in Spain, over six years and analysed the distribution of bTB to ultimately assess the likelihood of spatial and movement‐mediated transmission. We analysed movement and bTB data from 27, 633 units located in the region, of which 87% were involved in 1.4 million movements of 8.8 million animals. Network‐level connectivity was low, although a few highly connected units were identified. Up to 15% of the herds became bTB‐positive at some point during the study, with the highest percentage found in bullfighting and beef herds. Although bTB‐positive herds had a significantly higher degree and moved more cattle than negative herds. Results of the k ‐test, a permutation‐based procedure, suggested that positive farms were not significantly clustered in the movement network. Location was a likely risk factor as bTB‐positive farms tended to be located within 5 km from each other. Results suggested that movements may be a source of bTB in cattle in Castilla y Leon, although local factors may be more influential in determining risk of disease at the farm level. The description of the movement network in Castilla y Leon may be valuable for bTB surveillance in Spain. Moreover, results are useful to assess the movement‐associated risk for multiple diseases.